2003
DOI: 10.1210/en.2002-220703
|View full text |Cite
|
Sign up to set email alerts
|

Rat Anterior Pituitary Folliculostellate Cells Are Targets of Interleukin-1β and a Major Source of Intrapituitary Follistatin

Abstract: Folliculostellate cells of the anterior pituitary are postulated to be an important source of factors, such as follistatin, that regulate pituitary function by intercellular communication. To gain further insight into the function of this cell type, folliculostellate cells were enriched from cultured rat anterior pituitary cells, and an immortalized cell line designated FS/D1h was established and characterized. These FS/D1h cells express S100 immunoreactivity and produce IL-6 but not pituitary hormones such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 59 publications
2
49
0
Order By: Relevance
“…Several lines of evidence suggest that this reflects the transcriptional activation of the follistatin gene in pituitary gonadotropes (39). To better understand this mechanism and identify a suitable cell line for further studies, activin effects on follistatin mRNA expression were evaluated in greater detail in RAP cells and compared with those of gonadotrope-derived ␣T3-1 cells.…”
Section: Activin Increases Follistatin Transcript Levels Of Primary Ratmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of evidence suggest that this reflects the transcriptional activation of the follistatin gene in pituitary gonadotropes (39). To better understand this mechanism and identify a suitable cell line for further studies, activin effects on follistatin mRNA expression were evaluated in greater detail in RAP cells and compared with those of gonadotrope-derived ␣T3-1 cells.…”
Section: Activin Increases Follistatin Transcript Levels Of Primary Ratmentioning
confidence: 99%
“…In L␤T2 cells, the same fragment is a target of GnRH (37) but not of activin A in ␣T3-1 cells (38). On the other hand, a luciferase reporter construct designated rFS(rin3)-luc that incorporates ϳ2.8 kb of the 5Ј-flanking sequence and extends into the third intron of the rat follistatin gene is induced by activin in ␣T3-1 cells (39). Finally, it has been reported that the human follistatin promoter is activated in HepG2 cells by Smad signaling, downstream of activin or TGF-␤ (40,41).…”
mentioning
confidence: 99%
“…This SBE1 element preferentially binds Smad3 and mediates downstream effects of activin A. Luciferase reporter constructs that incorporate up to 2.86 kb of the upstream promoter of the rat Fst, but lack the intronic SBE1 enhancer, are unresponsive to activin signaling in either ␣T3-1 or L␤T2 cells (29,35,41). By contrast, the same reporters display both basal and Smad-dependent inducible activity when transfected into HepG2 or HEK293T cells, indicating that the function of SBE1 is dispensable in these cell types.…”
mentioning
confidence: 99%
“…Moreover, release and hypophyseal expression of IL-6 are considerably reduced in mutant mice for IL-1b [75]. It has also been demonstrated that IL-1b increases the production of IL-6 in cultures of rat folliculo-stellate cells [76]; these cells are considered a source of organspecific stem cells in the anterior pituitary gland [77,78], and they have been shown to be major producers of IL-6 in the adult pituitary [79]. These data, along with the similarity in the time-space expression of IL-1b and IL-6, and the coexpression of both interleu- kins in pituitary cells detected by us, suggest that IL-1b could exert a control on IL-6 expression during embryonic development, similarly to adult folliculo-stellate cells.…”
Section: Possible Interaction Between Il-1b and Il-6 In The Developinmentioning
confidence: 99%